The Influence of Wordwall Game Media on Students' Creativity and Conceptual Understanding in Elementary Schools - Rahmatullah Mulyono Widodo; Eges Triwahyuni; Ahmad Zaki Emyus (Jurnal Penelitian Pendidikan IPA, 2025)
Creativity and conceptual understanding are the main components in supporting more meaningful learning, because students are not only required to memorize information, but also to use it creatively in real life situations. This study aims to describe the effect of Wordwall Game Media on creativity and conceptual understanding of elementary school students. This type of research is a quasi-experimental study. The data collection technique is a creativity test and conceptual understanding. The results of the study show that the use of Wordwall Game Media has a significant influence on increasing creativity and conceptual understanding of elementary school students, value of creativity is 0.115 and the sig. value of conceptual understanding is 0.773. The use of this media has been proven to improve students' creative thinking skills, including fluency, flexibility, and elaboration of ideas, as well as deepening their conceptual understanding through more interesting and applicable interactions. Several recommendations can be suggested so that teachers and education practitioners consider the use of Wordwall Game Media as a learning aid to improve students' creativity and conceptual understanding. Further research can be conducted to explore the effectiveness of this media in various subjects and levels of education.